Socially sustainable urban renewal in emerging economies: A comparison of Magdolna Quarter, Budapest, Hungary and Albert Park, Durban, South Africa - Nzimande, Ntombifuthi Precious; Fabula, Szabolcs (Hungarian Geographical Bulletin, 2020)
This study compares the social sustainability of urban renewal interventions in Hungary and South Africa. The societal and environmental challenges arising from urbanisation and the associated population growth in major urban centres around the world have increased the research and policy foci on urban sustainability and governance. While urban regeneration projects are vitally important to urban sustainability, these interventions have been widely criticised because social sustainability issues have been overlooked or ignored. Therefore, there is a need for governance practices that are applicable to different national and urban contexts. The main aim of this study is twofold: firstly, it provides a literature review on the social sustainability of urban renewal and secondly, it compares urban renewal interventions in two different geographical settings to provide recommendations about public participation and stakeholder involvement, which can contribute to increasing social sustainability of urban renewal projects. To this end, a comparative approach was adopted through the analysis of two urban renewal projects: Magdolna Quarter Programme (Budapest, Hungary) and the Albert Park (Durban, South Africa), the data for which were based on a review of secondary sources, including international literature and policy documents. It was found that although urban renewal serves a city-wide purpose (and not just a local one), the socio-economic impacts of these projects have not yet been adequately explored. Furthermore, to achieve higher urban renewal sustainability, there is a need for impact assessments (with special attention paid to the social effects) to promote public participation and empowerment.